Cell type identification, differential expression analysis and trajectory inference in single-cell transcriptomics - Smolander, Johannes (fi=Turun yliopisto|en=University of Turku|, 2023)
Single-cell RNA-sequencing (scRNA-seq) is a cutting-edge technology that enables to quantify the transcriptome, the set of expressed RNA transcripts, of a group of cells at the single-cell level. It represents a significant upgrade from bulk RNA-seq, which measures the combined signal of thousands of cells. Measuring gene expression by bulk RNA-seq is an invaluable tool for biomedical researchers who want to understand how cells alter their gene expression due to an illness, differentiation, ternal stimulus, or other events. Similarly, scRNA-seq has become an essential method for biomedical researchers, and it has brought several new applications previously unavailable with bulk RNA-seq. scRNA-seq has the same applications as bulk RNA-seq. However, the single-cell resolution also enables cell annotation based on gene markers of clusters, that is, cell populations that have been identified based on machine learning to be, on average, dissimilar at the transcriptomic level. Researchers can use the cell clusters to detect cell-type-specific gene expression changes between conditions such as case and control groups. Clustering can sometimes even discover entirely new cell types. Besides the cluster-level representation, the single-cell resolution also enables to model cells as a trajectory, representing how the cells are related at the cell level and what is the dynamic differentiation process that the cells undergo in a tissue. This thesis introduces new computational methods for cell type identification and trajectory inference from scRNA-seq data. A new cell type identification method (ILoReg) was proposed, which enables high-resolution clustering of cells into populations with subtle transcriptomic differences. In addition, two new trajectory inference methods were developed: scShaper, which is an accurate and robust method for inferring linear trajectories; and Totem, which is a user-friendly and flexible method for inferring tree-shaped trajectories. In addition, one of the works benchmarked methods for detecting cell-type-specific differential states from scRNA-seq data with multiple subjects per comparison group, requiring tailored methods to confront false discoveries. KEYWORDS: Single-cell RNA sequencing, transcriptome, cell type identification, trajectory inference, differential expression

Yksisoluinen RNA-sekvensointi on huipputeknologia, joka mahdollistaa transkriptomin eli ilmentyneiden RNA-transkriptien laskennallisen määrittämisen joukolle soluja yhden solun tarkkuudella, ja sen kehittäminen oli merkittävä askel eteenpäin perinteisestä bulkki-RNA-sekvensoinnista, joka mittaa tuhansien solujen yhteistä signaalia. Bulkki-RNA-sekvensointi on tärkeä työväline biolääketieteen tutkijoille, jotka haluavat ymmärtää miten solut muuttavat geenien ilmentymistä sairauden, erilaistumisen, ulkoisen ärsykkeen tai muun tapahtuman seurauksena. Yksisoluisesta RNA-sekvensoinnista on vastaavasti kehittynyt tärkeä työväline tutkijoille, ja se on tuonut useita uusia sovelluksia. Yksisoluisella RNA-sekvensoinnilla on samat sovellukset kuin bulkki-RNA-sekvensoinnilla, mutta sen lisäksi se mahdollistaa solujen tunnistamisen geenimarkkerien perusteella. Geenimarkkerit etsitään tilastollisin menetelmin solupopulaatioille, joiden on tunnistettu koneoppimisen menetelmin muodostavan transkriptomitasolla keskenään erilaisia joukkoja eli klustereita. Tutkijat voivat hyödyntää soluklustereita tutkimaan geeniekspressioeroja solutyyppien sisällä esimerkiksi sairaiden ja terveiden välillä, ja joskus klusterointi voi jopa tunnistaa uusia solutyyppejä. Yksisolutason mittaukset mahdollistavat myös solujen mallintamisen trajektorina, joka esittää kuinka solut kehittyvät dynaamisesti toisistaan geenien ilmentymistä vaativien prosessien aikana. Tämä väitöskirja esittelee uusia laskennallisia menetelmiä solutyyppien ja trajektorien tunnistamiseen yksisoluisesta RNA-sekvensointidatasta. Väitöskirja esittelee uuden solutyyppitunnistusmenetelmän (ILoReg), joka mahdollistaa hienovaraisia geeniekspressioeroja sisältävien solutyyppien tunnistamisen. Sen lisäksi väitöskirjassa kehitettiin kaksi uutta trajektorin tunnistusmenetelmää: scShaper, joka on tarkka ja robusti menetelmä lineaaristen trajektorien tunnistamiseen, sekä Totem, joka on käyttäjäystävällinen ja joustava menetelmä puumallisten trajektorien tunnistamiseen. Lopuksi väitöskirjassa vertailtiin menetelmiä solutyyppien sisäisten geeniekspressioerojen tunnistamiseen ryhmien välillä, joissa on useita koehenkilöitä tai muita biologisia replikaatteja, mikä vaatii erityisiä menetelmiä väärien positiivisten löydösten vähentämiseen. ASIASANAT: yksisoluinen RNA-sekvensointi, klusterointi, trajektorin tunnistus, geeniekspressio